PENGGUNAAN VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS 4 SD - Wijaya, Herry; Dewi, Anggralita Sandra; Dewi, Galuh Kartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
An observable improvement in fourth-grade students’ achievement in Natural and Social Sciences (IPAS) was recorded after animated instructional videos were incorporated into classroom activities at SD Cendekia Sidoarjo. This classroom-based inquiry emerged from the initial finding that a considerable number of learners had not yet satisfied the established mastery standards. To address this issue, a Classroom Action Research (CAR) framework was employed, with YouTube utilized as a supporting learning resource. The intervention was carried out across three stages: a pre-cycle, followed by Cycle I and Cycle II. Each stage involved a sequence of planning, implementation, observation, and reflection. The collected data indicated a gradual rise in students’ average scores, moving from 68.235 in the pre-cycle to 74.706 in Cycle I, and eventually reaching 77.059 in Cycle II. In line with this pattern, the level of classical mastery also showed marked progress, increasing from 35.29% to 47.05%, and finally achieving 82.35% by the end of Cycle II. These findings demonstrate that integrating animated video media into instruction supported better learning performance among fourth-grade students in the IPAS subject.